A comparative study on the effectiveness of low level laser and ibuprofen in pain control after extraction - Roxas, Maria Carmela N.
A comparative study of the analgesic effects of pre-operatively administered Ibuprofen and Low Level Laser Therapy on postoperative pain after simple extraction of teeth was undertaken in 25 patients in single blind, cross-over trial. Patients estimate the intensity of pain with a scale of 0,1,2,3, at 3 time points after extraction, namely at the 4th, 8th and 12th hour. The results of this study shows that in simple extraction cases, there is no significant difference in the post-analgesic effect pre-treatment with Ibuprofen or with Low level laser. The severity of pain recorded was almost always mild pain and as such most patients did not require any post-operative analgesia thus the onset of post-operative pain was not recorded. However, mean pain scores for the 4th hour was less in those pre-treated with the Portable Laser System but the difference was not significant.